Implementasi Aplikasi Quizizz Sebagai Media Pembelajaran Bahasa Inggris Siswa Kelas V SDN 4 Kuranji - Yuliandini, Audi; Rosidik, Izam; Wulandari, Nourma Pramestie (Rengganis Jurnal Pengabdian Masyarakat, 2025)
Technology plays a crucial role in enhancing students' interest and understanding, particularly at the elementary school level. Therefore, students from the Faculty of Teacher Training and Education at the University of Mataram, participating in the 8th cohort of the Kampus Mengajar program and placed at SDN 04 Kuranji, developed the "Play with Quizizz" program. This article explores the implementation of Quizizz as a tool for teaching fifth-grade students at SDN 4 Kuranji using English. The program aimed to improve vocabulary acquisition, boost students' motivation to learn, and assist teachers in creating an interactive and engaging learning environment. The community service initiative involved several stages, including planning, implementation, and evaluation or refinement. The results demonstrated an increase in students' classroom engagement, as well as improvements in vocabulary and grammar comprehension. This article recommends the use of Quizizz as an innovative alternative learning medium, which can also be applied to other subjects to enhance the overall quality of education.